614. Pharmacodynamics (PD) of the Beta-Lactamase Inhibitor Xeruborbactam When Administered as the Oral Prodrug in Combination with Ceftibuten. (15th December 2022) - Tarazi, Ziad; Roos, Niki; Page, Ted; Griffith, David
Abstract: Background: Xeruborbactam (XERU) is a member of a new class of cyclic boronic acid β-lactamase inhibitors with inhibitory activity against major members of Class A, B, C, and D beta-lactamases. XERU is highly orally bioavailable when administered as the isobutyryloxymethyl prodrug, with a long terminal plasma half-life that supports once daily dosing. The purpose of these studies was to determine the pharmacodynamic parameter that best described the activity of XERU administered as the oral prodrug in combination with a fixed dosage regimen of ceftibuten in the neutropenic mouse thigh infection model. %24h Free Xeruborbactam Time > 4 mg/L 24h Free Xeruborbactam AUC Methods: Three E. coli and five K. pneumoniae isolates were used in these studies. Ceftibuten MICs (with 4 mg/L XERU) ranged from 0.125 to 2 mg/L and included strains with ESBLs and KPC. Mice were rendered neutropenic, infected with ∼10 7 CFU/thigh and were treated with various doses of XERU in combination with ceftibuten (50 mg/kg q6h) by the PO route starting 2 hours post infection for 24 hours. The ceftibuten dosage regimen was designed to simulate once daily 800 mg oral doses in humans obtained from a previous Phase 1 study. Plasma exposures (PK) were measured in neutropenic, infected mice. The relationship between PK-PD indices and the reduction in the log number of CFU per thigh were analyzed by using the sigmoid maximum (Emax) PD model. Results: The activity of xeru was best described by the % 24h free xeru plasma concentrations exceeded 4 mg/L and 24h free XERU plasma AUC. Xeru PK-PD Parameters in Combination with Ceftibuten Xeru PK-PD Parameter R 2 Magnitude Required Stasis 1-log kill %24h Free Xeru > 4 mg/L 0.81 8.85 15.37 24h Free Xeru AUC 0.84 30.03 76.58 Conclusion: The PK-PD of XERU administered as the oral prodrug in combination with ceftibuten, and the clinical PK of both drugs support once-daily dosing for the treatment of cUTIs due to Enterobacterales, including ESBL- and carbapenemase-producing strains. Disclosures: Ziad Tarazi, Qpex Biopharma: Employee Niki Roos, n/a, Qpex Biopharma: Employee Ted Page, n/a, Qpex Biopharma: Employee David Griffith, n/a, Qpex Biopharma: Employee.